Do Product Knowledge and Halal Awareness Influence Purchase Intention and Purchase Decision Of Korean Instant Noodles Among Generation Z? - Ghozani, Sobi; Andrean, Rizky; Jannah, Arina Roudhotul; Adinugraha, Hendri Hermawan (Sharia Economics Study Program Faculty of Islamic Economics and Business UIN Sunan Gunun, 2025)
Korean culture, which is global and popular among the younger generation, including in Indonesia, also influences their preferences in the fields of clothing, music, cosmetics, and food. Using the mediating variable of purchase intention, this research attempts to examine how product knowledge and halal awareness affect the decision to buy Korean instant noodles among generation Z in the Pekalongan Ex-Residency. This study uses a quantitative method by 160 members of generation Z who were selected using Hair theory made up the sample for this study. The incidental sampling is employed in this research. A Likert scale questionnaire is used to collect data for this investigation. Path analysis using the Sobel test is the data analysis method employed in this investigation. The findings of the study show that purchasing intention is influenced by halal awareness and product knowledge. Purchase intention, halal awareness, and product understanding all affect the decision to buy. The impact of halal awareness and product knowledge on purchasing decisions is mediated by purchase intention.